(untitled) (Journal of Entrepreneurship and Business, 2021)
New world today has come out with many technology in helping us to ease our daily live. This includes creating a new system in e –commerce. Among the latest upgraded technology that arise during these days are the ability to use smart phone for buying and purchasing purpose. Like many other industries, food industry is currently effected with massive development of systems in providing better services and quality in terms of food ordering, selecting and delivery. The purpose of this study is to determine the factors effecting the students’ choices towards online food delivery. The quantitative research method was chosen and the questionnaire was used to collect data as a survey method. Structured questionnaire was used in this study. There were 265 respondents who were randomly included in the questionnaires conducted by the researcher. The data was analyzed using Google form and questionnaire. The data collected was analyzed by using Statistical Packages for Social Science Version 25 (SPSS Version 25) software based on descriptive analysis, reliability analysis, and correlation analysis. As for the result, all of the independent variables (attitudes, time saving, and promotion) that had been studied in this research had significant relationships towards dependent variable (consumer behavior). The result of the research objectives which is to examine the relationship between attitudes, time saving and promotion that influencing consumer behavior towards Online Food Delivery.